The Role of XPB/Ssl2 dsDNA Translocase Processivity in Transcription Start-site Scanning. Issue 14 (9th July 2021) - Tomko, Eric J.; Luyties, Olivia; Rimel, Jenna K.; Tsai, Chi-Lin; Fuss, Jill O.; Fishburn, James; Hahn, Steven; Tsutakawa, Susan E.; Taatjes, Dylan J.; Galburt, Eric A.
Graphical abstract: Highlights: Differences in transcription start-site usage between S . cerevisiae and H. sapiens are not understood. Properties of S. cerevisiae and H. sapiens dsDNA translocases within TFIIH differ. Relative processivities of Pol II and TFIIH translocases (Ssl2/XPB) can explain start-site usage. Kinase module of S . cerevisiae activates Ssl2 processivity, leading to downstream scanning. Abstract: The general transcription factor TFIIH contains three ATP-dependent catalytic activities. TFIIH functions in nucleotide excision repair primarily as a DNA helicase and in Pol II transcription initiation as a dsDNA translocase and protein kinase. During initiation, the XPB/Ssl2 subunit of TFIIH couples ATP hydrolysis to dsDNA translocation facilitating promoter opening and the kinase module phosphorylates Pol II to facilitate the transition to elongation. These functions are conserved between metazoans and yeast; however, yeast TFIIH also drives transcription start-site scanning in which Pol II scans downstream DNA to locate productive start-sites. The ten-subunit holo-TFIIH from S. cerevisiae has a processive dsDNA translocase activity required for scanning and a structural role in scanning has been ascribed to the three-subunit TFIIH kinase module. Here, we assess the dsDNA translocase activity of ten-subunit holo- and core-TFIIH complexes (i.e. seven subunits, lacking the kinase module) from both S. cerevisiae and H. sapiens . We find that neither holo nor core human TFIIH exhibit processive translocation, consistent with the lack of start-site scanning in humans. Furthermore, in contrast to holo-TFIIH, the S. cerevisiae core-TFIIH also lacks processive translocation and its dsDNA-stimulated ATPase activity was reduced 5-fold to a level comparable to the human complexes, potentially explaining the reported upstream shift in start-site observed in vitro in the absence of the S. cerevisiae kinase module. These results suggest that neither human nor S. cerevisiae core-TFIIH can translocate efficiently, and that the S. cerevisiae kinase module functions as a processivity factor to allow for robust transcription start-site scanning.